THE INFLUENCE OF EXERCISE TEACHING STYLE TOWARD STUDENTS’ LONG JUMP ABILITY IN FACULTY OF SPORT SCIENCE UNIVERSITAS NEGERI MANADO - PODUNG, BEATRIX J. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the influence of teaching style exercise on long jump ability in athletics students of Sport Education Department Faculty of Sport Science Universitas Negeri Manado. The method used in this study is the experimental method, namely by conducting field experiments in the form of teaching style. The research design used in this study refers to the experimental design by Randomized Control Group Pre-Test and Post Test Design. The population in this study were all students of Sport Education Department Faculty of Sport Science Universitas Negeri Manado, which amounted to 94 students, the sample in this study researchers limit the number of 20 people taken randomly and then divided into two groups of 10 each experiment group and 10 people in the control group. The research instrument used in this study was: "Skipping Capability". To test the hypotheses in this study used the t-test statistics (Sudjana, 1990: 232) with a significance level α = 0.05. The results obtained in this study were tob = 7.347> ttab = 2.101 for Ho was rejected and accepted Ha which stated the average long jump ability in the experimental group given the teaching and learning style of the exercise was greater than the average long jump ability in the control group. Therefore, this study shows there is an influence of the teaching style on increasing the long jump ability of the students of Sport Education Department Faculty of Sport Science Universitas Negeri Manado.